Adjuvant chemotherapy for lymph node positive esophageal squamous cell cancer: The prediction role of low mean platelet volume - Liu, Xiaoling; Zhang, Kaijiong; Tang, Jie; Jiang, Li; Jiang, Yu; Wang, Qifeng (Frontiers in Oncology, 2022)
Background: This study aimed to examine whether MPV is a useful prognostic marker and investigated whether MPV is a risk factor that helps identify patients with locally advanced-stage ESCC who will most likely benefit from adjuvant chemotherapy. Methods: Patients (n =1690) with histologically confirmed ESCC were diagnosed with locally advanced stage (pT3-4N0M0 and pT1-4N+M0) at Sichuan Cancer Hospital from 2009 to 2017. Clinicopathological factors and platelet-related values were tested for their associations with survival using univariate and multivariate Cox regression analyses. The KM curve continuous variable analysis was performed to identify the optimal cut-off value for MPV. Cumulative survival rates were determined using the Kaplan–Meier estimator and compared using the log-rank test. Results: Multivariate analysis indicated that low MPV was an important risk factor for overall survival in locally advanced ESCC, independent of classic clinicopathological factors. The optimal cut-off value of MPV (11.8 fL) was used to stratify high-risk patients. Patients with low mean platelet volumes had a worse prognosis than those with larger platelet volumes, according to Kaplan–Meier analysis and the log-rank test. Patients diagnosed with a pathological lymph node-positive stage with a low MPV (≤11.8 fL) benefited from postoperative chemotherapy, but not those with a high-level MPV (>11.8 fL). Conclusion: MPV served as an independent predictor of prognosis of locally advanced-stage ESCC and predicted a survival benefit conferred by postoperative adjuvant chemotherapy in lymph node-positive ESCC.